Physical Fitness and Skeletal Muscle Mass During Neoadjuvant Chemoradiotherapy in Patients with Locally Advanced Rectal Cancer: An Observational Study. Issue 4 (October 2021) - Heldens, Aniek F. J. M.; Bongers, Bart C.; de Vos-Geelen, Judith; Minis-Rutten, Iris J.; Stassen, Laurents P.; Buhre, Wolfgang F.; van Meeteren, Nico L.
Abstract : Background: Patients with locally advanced rectal cancer are often considered for neoadjuvant chemoradiotherapy before resection. This presurgical treatment can have negative effects on physical fitness, muscle mass, and treatment compliance, which can negatively influence clinical outcomes. Objective: The aim of this study was to evaluate physical fitness and skeletal muscle mass before and after neoadjuvant chemoradiotherapy in single subjects with locally advanced rectal cancer. Design: An observational longitudinal study of single subjects. Methods: Routine care data were retrospectively analyzed. Data consisted of tumor characteristics, clinical data (eg, side effects and toxicity of the neoadjuvant chemoradiotherapy, loss of body mass), data on performance-based physical fitness, and computed tomography–derived skeletal muscle mass. An independent-samples t test or its nonparametric equivalent was performed on outcome measures to test for significant differences between T 0 and T 1 . For comparing several subgroups in this cohort, the Mann-Whitney U test was performed and correlations were studied using the Pearson or Spearman correlation coefficient, as appropriate. Results: Data from 25 single subjects were available. Aerobic capacity (n = 25, P = .033) and skeletal muscle mass (n = 16, P = .005) were significantly reduced after neoadjuvant chemoradiotherapy. Although not statistically significant, a large number of patients demonstrated a decrease in muscle strength and functional mobility after completing neoadjuvant chemoradiotherapy. In 14 patients (56%), adverse events, dose-limiting toxicity, or early termination of treatment occurred. Conclusions: Aerobic capacity and skeletal muscle mass decreased following neoadjuvant chemoradiotherapy, with large interindividual differences concerning the changes in physical fitness and muscle mass. This between-subject variability indicates the importance of a personalized treatment approach.